Pemulihan Residen Dengan Family Support Group (FSG) di Loka Rehabilitasi BNN Deli Serdang - Four Five Sanwita Kabeakan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to find out how the Family Support Group is implemented in supporting Resident recovery carried out at the Deli Serdang BNN Rehabilitation Center. The method used in this research is a qualitative method collected through interviews and documentation with Counselors, Residents and Resident Families. The author conducted interviews with two residents, family and counselor. The research results show that the Family Support Group provides reinforcement to residents in the recovery and rehabilitation process, so family support is very necessary for resident recovery by providing motivation to residents. Support provided by families includes seminars, sharing, counseling for families with counselors, and family dialogue. Through this support, residents receive full praise and support so that residents can recover and be ready to return to society.